The physical and biological constraints that hinder the development of physical abilities and energy reserves in elite kayakers and canoeists - Makarova, G. A.; Pogrebnoy, A. I.; Karpov, A. A.; Chernukha, S. M. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to investigation of medical and biological factors that could impede the enhancement of the training performance among elite kayakers and canoeists.